Periodontitis y enfermedad cardiovascular: Una actualización: Periodontitis and cardiovascular disease: An update - Falcón-Guerrero, Britto Ebert (2022)
Periodontitis is an inflammatory disorder, initiated by the presence of bacterial plaque, which affects both the periodontal ligament and the bone that surrounds the teeth. These ailments include cardiovascular disease, gastrointestinal and colorectal cancer, diabetes and insulin and Alzheimer's disease, as well as respiratory tract disease and adverse events of pregnancy. In recent decades, several lines of evidence have supported the existence of a relationship between periodontitis and systemic health. Periodontitis acts within the same chronic inflammatory model seen in cardiovascular disease, it is now evident that cardiac disorders are worsened by periodontitis, both experimentally and in humans. For all these reasons, it is highly plausible that the prevention of periodontal lamina alteration has an impact on the progression of cardiovascular alterations. In this review, we have provided an updated account of the current understanding of periodontitis and cardiovascular disease.